PENDIDIKAN LITERASI DIGITAL MELALUI MEDIA GOOGLE PLAY BOOKS - Sudarsri Lestari; Erisy Syawiril Ammah (INCARE, International Journal of Educational Resources, 2021)
The digital literacy education described in this paper is in line with the concept developed by UNESCO. Digital literacy education is related to the process of strengthening skills (life skills) which does not only involve the ability to use technology, information and communication devices. But also the ability to socialize, the ability to learn, think critically, creatively, and inspire as a form of digital competence. Digital literacy education is an important foundation in understanding technology, information and communication tools. Digital literacy education can be built and strengthened by accessing various information and communication in various forms in digital media, especially through google play books. It is through this media that digital literacy education can be developed according to its objectives, namely to understand, create, and collaborate on technology effectively. Digital literacy education must always develop in line with the changing era, especially in the 21st era which demands comprehensive digital literacy skills.